The Role of Perceived Risk and Satisfaction as Mediators Between Service Quality and Tourist Loyalty in SPA Tourism in Ubud - Putra, Dewa Putu Kiskenda Erwanda Putra; Wiranatha, AA Suryawan (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2025)
The spa tourism industry in Ubud has grown rapidly, with 96 spas operating in both Day Spa and Hotel or Resort Spa categories. The Spa industry as a tourist attraction in Ubud is expected to provide satisfactory quality of services and make tourists as their loyal customers. This study investigates the mediating roles of tourist satisfaction and perceived risk in the relationship between service quality and tourist loyalty. The aim of this research is to ensure that the marketing of Spa tourism as a developed industry in Ubud is always able to provide quality services that satisfy the tourists’ expectations by confirming the dimension of Spa services in Ubud. Using a quantitative approach with Structural Equation Model (SEM) among variables of service quality; Tourist loyalty; Perceived risk and satisfaction, data were collected from 213 foreign tourists through purposive sampling . The findings reveal that service quality significantly influences satisfaction, which in turn significantly affects loyalty. Satisfaction fully mediates the effect of service quality on loyalty, whereas perceived risk does not play a significant mediating role. These insights highlight the importance of delivering consistently high-quality spa services to enhance tourist satisfaction and loyalty in wellness tourism.